Singapore : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This Selected Issues paper assesses the stability of Singapore's banking system in a regional context. It proposes a novel methodology for gauging domestic financial stability. The paper assesses the impact of fiscal measures on macroeconomic activity, and analyzes the effects of monetary policy using structural vector autoregressions. Estimates show that the Monetary Authority of Singapore's exchange rate-centered framework is well suited to shape monetary decision making, given the large impact that changes in the nominal exchange rate have on activity and prices.